Exogenous Orexin-A Microinjected Into Central Nucleus of the Amygdala Modulates Feeding and Gastric Motility in Rats - Jin, Tingting; Jiang, Zhongxin; Luan, Xiao; Qu, Zhuling; Guo, Feifei; Gao, Shengli; Xu, Luo; Sun, Xiangrong (Frontiers in Neuroscience, 2020)
ABSTRACT Orexin-A is a circulating neuropeptide and neurotransmitter that regulates food intake and gastric motility. The central nucleus of the amygdala (CeA), which regulates feeding behavior and gastric function, expresses the orexin-1 receptor. The aim of this study was to evaluate the effects of microinjection of exogenous orexin-A into the CeA on food intake and gastric motility, and to explore the mechanisms of these effects. Normal chow and high fat food (HFF) intake were measured, gastric motility and gastric emptying were evaluated, extracellular single unit firing was recorded, and c-fos expression was determined. The results showed that microinjection of orexin-A into the CeA resulted in increased HFF intake, but did not affect normal chow intake. This effect was blocked by an orexin-1 receptor antagonist-SB-334867 and was partially blocked by a dopamine D1 receptor antagonist-SCH-23390. Gastric motility and gastric emptying were enhanced by orexin-A, and the former effect was abolished by subdiaphragmatic vagotomy. The firing frequency of gastric distention-related neurons was regulated by orexin-A via the orexin-1 receptor. Furthermore, c-fos expression was increased in the ventral tegmental area (VTA) and the nucleus accumbens (NAc) (reward center), the lateral hypothalamus (LHA; the feeding center), and the dorsal motor nucleus of the vagus (DMV; vagal motor center) in response to microinjection of orexin-A into the CeA. These findings showed that orexin-A regulated palatable foot intake and gastric motility via the CeA. The LHA, the VTA, and the NAc may participate in palatable food intake and the CeA-DMV-vagus-stomach pathway may be involved in regulating gastric motility through regulation of neuronal activity in the CeA.